The cultivation of human multipotent mesenchymal stromal cells in clinical grade medium for bone tissue engineering - Pytlík, Robert; Stehlík, David; Soukup, Tomáš; Hubálek Kalbáčová, Marie; Rypáček, František; Trč, Tomáš; Mulinkova, Katarina; Michnova, Petra; Kideryová, Linda; Živný, Jan; Klener, Pavel; Veselá, Romana; et al. (Biomaterials, 2009)
Clinical application of human multipotent mesenchymal stromal cells (hMSCs) requires their expansion to be safe and rapid. We aimed to develop an expansion protocol which would avoid xenogeneic proteins, including fetal calf serum (FCS), and which would shorten the cultivation time and avoid multiple passaging. First, we have compared research-grade alpha-MEM medium with clinical grade CellGro for Hematopoietic Cells' Medium. When FCS was used for supplementation and non-adherent cells were discarded, both media were comparable. Both media were comparable also when pooled human serum (hS) was used instead of FCS, but the numbers of hMSCs were lower when non-adherent cells were discarded. However, significantly more hMSCs were obtained both in alpha-MEM and in CellGro supplemented with hS when the non-adherent cells were left in the culture. Furthermore, addition of recombinant cytokines and other supplements (EGF, PDGF-BB, M-CSF, FGF-2, dexamethasone, insulin and ascorbic acid) to the CellGro co-culture system with hS led to 40-fold increase of hMSCs' yield after two weeks of cultivation compared to alpha-MEM with FCS. The hMSCs expanded in the described co-culture system retain their osteogenic, adipogenic and chondrogenic differentiation potential in vitro and produce bone-like mineralized tissue when propagated on 3D polylactide scaffolds in immunodeficient mice. Our protocol thus allows for very effective one-step, xenogeneic protein-free expansion of hMSCs, which can be easily transferred into good manufacturing practice (GMP) conditions for large-scale, clinical-grade production of hMSCs for purposes of tissue engineering.
Keywords: dospělí; Animals; mezibuněčné signální peptidy a proteiny; Female; mezenchymální kmenové buňky; buňky stromatu; Cytokines; Adult; Intercellular Signaling Peptides and Proteins; ženské pohlaví; mladý dospělý; cytokiny; kosti a kostní tkáň; buněčná diferenciace; lidé; tkáňové inženýrství; Multipotent Stem Cells; Mice; myši inbrední NOD; Aged, 80 and over; Culture Media; transplantace mezenchymálních kmenových buněk; myši; Mesenchymal Stem Cells; Male; Mesenchymal Stem Cell Transplantation; kultivační média; Aged; Mice, Inbred NOD; Young Adult; Stromal Cells; lidé středního věku; Cell Differentiation; senioři nad 80 let; buněčné kultury; senioři; zvířata; mužské pohlaví; Cell Culture Techniques; Tissue Engineering; Bone and Bones; Middle Aged; multipotentní kmenové buňky; Humans